An integrated system for advanced monitoring and control of fed-batch fermentations of recombinant E. coli. - Rocha, I. (2002)
A system for the on-line monitoring of the major state variables during the production of recombinant proteins with E. coli was developed. Substrate (glucose) and the major by-product (acetate) were measured with a Flow Injection Analysis system, while the carbon dioxide and oxygen transfer rates were calculated from data obtained with exhaust gas analysis. The fermentation culture weight was also continuously assessed with a balance placed below the fermenter, allowing the use of more precise mass-based concentrations. The graphical programming environment LabVIEW was used to acquire and integrate these variables in a supervisor computer, allowing to perform integrated monitoring and control of the process. This framework is illustrated with different experiments for model calibration, state estimation by software sensors and process performance optimisation by exponential feed control.